ELKE HENTSCHEL, THEO HARDEN: EINFÜHRUNG IN DIE GERMANISTISCHE LINGUISTIK: Bern etc., Peter Lang, 2014, 238 str. ISBN 978-0343-1740-5 (print), ISBN 978-3-0353-0640-8 (eBook) - Jesenšek, Vida (Slavia Centralis, 2020)
The author presents Introduction to Germanic Linguistics (2014), which consists of 16 chapters on selected areas of research in (Germanic) languages.